Development of Data Models on Cooperative Systems - Sugiarto Sugiarto; Evi Triandini; Chrystia Aji Putra; Riko Setya Wijaya (CCIT Journal, 2023)
The information system used by cooperatives is generally an accounting information system because it has transaction processes, ledgers, and processes various accounting reports such as balance sheets, cash flows, and profit and loss. The Patria Karya Bersama Cooperative is a cooperative entity engaged in the field of Service Cooperatives where the main service sector is in Tourism. At the present time the condition of the Patria Karya Bersama Cooperative is carrying out all semi-manual administrative processes because some of the data processing processes have utilized computers and data processing aids, but most of them still use handwriting. This study builds a data model that can later be used to build a cooperative system database. The method used for the development of the data model in this study is the Data Base Life Cycle (DBLC) method. The model has several stages of work and will also produce several data models. However, this article only describes the results of research that produces a data model in the form of an E-R Diagram. The use of this method has provided convenience, accuracy and compatibility between the data requirements needed according to the Cooperative Patria Karya Bersama business process. The data model in the form of an E-R diagram has been generated in this study. The data model design of the cooperative information system model resulted in ten entities. The design of the data model produced in this study will make it easier for database developers to build a comparative information system database.